Impacts of the Coronavirus crisis on the contractual stability of professional contracts in Sport - Kohout, D. (Acta Universitatis Carolinae Iuridica, 2021)
The covid-19 virus struck the global society with full power in the first months of the year 2020 and the sports industry was not spared from its impacts. This paper looks at the consequences that the pandemic had for the stability of professional contracts, mainly in the field of football and ice hockey;nevertheless, these observations could be applicable to other professional sport disciplines as well. The situation often brought tensions between the well-respected principle of contractual stability in sport and the acute needs of the clubs and players. It could be considered that even if the pandemic fades away one day, it will leave its footprints on the shape of professional sport. Besides general discussion of the legal consequences of the covid-19 pandemic for professional contracts this article also seeks to provide practical input by drafting a model covid clause for future professional sport contracts and by considering other possibilities of reflecting unforeseen global instances of force majeure in athletes` agreements.